Genome-wide pooling approach identifies SPATA5 as a new susceptibility locus for alopecia areata - Forstbauer, Lina M.; Ludwig-Peitsch, Wiebke (European journal of human genetics, 2012)
Alopecia areata (AA) is a common hair loss disorder, which is thought to be a tissue-specific autoimmune disease. Previous research has identified a few AA susceptibility genes, most of which are implicated in autoimmunity. To identify new genetic variants and further elucidate the genetic basis of AA, we performed a genome-wide association study using the strategy of pooled DNA genotyping (729 cases, 656 controls). The strongest association was for variants in the HLA region, which confirms the validity of the pooling strategy. The selected top 61 single-nucleotide polymorphisms (SNPs) were analyzed in an independent replication sample (454 cases, 1364 controls). Only one SNP outside of the HLA region (rs304650) showed significant association. This SNP was then analyzed in a second independent replication sample (537 cases, 657 controls). The finding was not replicated on a significant level, but showed the same tendency. A combined analysis of the two replication samples was then performed, and the SNP rs304650 showed significant association with P=3.43 × 10−4 (OR=1.24 (1.10-1.39)). This SNP maps to an intronic region of the SPATA5 (spermatogenesis-associated protein 5) gene on chromosome 4. The results therefore suggest the SPATA5 locus is a new susceptibility locus for AA.